Cardioprotection of (±)-sodium 5-bromo-2-(α-hydroxypentyl) benzoate (BZP) on mouse myocardium I/R injury through inhibiting 12/15-LOX-2 activity. (October 2019) - Xiao, Yue; Song, Chuanjun; Lin, Qiao; Shi, Xiaojing; Yu, Wenquan; Huang, Xin; Wang, Huimin; Chen, Yang; Wang, Ruiyong; Geng, Xuepeng; Qin, Mingyang; Hu, Kaizhao; et al.
Abstract: (±)-Sodium5-bromo-2-(α-hydroxypentyl) benzoate (brand name: brozopine, BZP, 1a ), derived from L-3- n -butylphthalide (L-NBP), has been reported to protect the brain from stoke and has been approved by CFDA in Phase I-II clinical trials. However, it remains to be investigated whether1a may exhibit any cardioprotective effect on ischemia-reperfusion (I/R) injury. In the current study, C57BL/6 and ICR mice were pretreated with1a, and myocardium I/R were then performed. We found that1a not only significantly reduced the infarct size and improved cardiac contractile function after acute MI/R in both species, but also protected hearts from chronic MI-related cardiac injury. Mechanically, we found that1a physically binds to 12/15-LOX-2 using molecular docking. The shRNA-mediated 12/15-LOX-2 knockdown almost completely blocked the protective effect of1a . Our findings, for the first time, strongly indicate that1a may serve as a potent and promising cardioprotective agent in treatment of I/R related injury, at least partially through targeting 12/15-LOX-2. Graphical abstract: Image 1 Highlights: Compound 1a improves the cardiac function after I/R ex vivo and in vivo. 1a improves MI-induced long term myocardial function and survival. 1a decreases I/R plasma creatine kinase, lactate dehydrogenase and iNOS activity. The cardioprotective effect of 1a is mediated through PI3K/Akt/NO signaling pathway. 1a protects against oxidative stress-induced cell damage via inhibiting 15-LOX-2.